Answer :

6x2 – 17ix – 12 = 0


Given 6x2 – 17ix – 12 = 0


6x2 – 17ix – 12 × 1 = 0


We have i2 = –1 1 = –i2


By substituting 1 = –i2 in the above equation, we get


6x2 – 17ix – 12(–i2) = 0


6x2 – 17ix + 12i2 = 0


6x2 – 9ix – 8ix + 12i2 = 0


3x(2x – 3i) – 4i(2x – 3i) = 0


(2x – 3i)(3x – 4i) = 0


2x – 3i = 0 or 3x – 4i = 0


2x = 3i or 3x = 4i



Thus, the roots of the given equation are and.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

–x2 + RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the fRD Sharma - Mathematics

Solve:
<
RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

x2 + 1RS Aggarwal - Mathematics